2000
DOI: 10.1097/00003226-200001000-00019
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis in UV-exposed Rabbit Corneas

Abstract: Apoptosis appears to be a mechanism of corneal cell death after UVR. The 310-nm UVR caused more extensive damage to the corneal stroma and endothelium than did the 280-nm UVR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
79
0
6

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(92 citation statements)
references
References 19 publications
7
79
0
6
Order By: Relevance
“…Podskochy et al (2000) have shown that UVB focused on the center of the un-wounded cornea of an anesthetized rabbit results in full thickness corneal damage with apoptosis of corneal epithelium, keratocytes, and corneal endothelial cells. Apoptosis of corneal epithelial cells, visualized by TUNEL staining and confirmed by electron microscopy, peaked at 24 hours post-UVR, as was seen in the current study; by 72 hours postexposure, keratocytes were completely absent from the exposed region of the cornea (Podskochy et al, 2000). By 7 days there was TOXICOLOGIC PATHOLOGY almost complete repopulation of the injured stroma by new keratocytes (Podskochy and Fagerholm, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Podskochy et al (2000) have shown that UVB focused on the center of the un-wounded cornea of an anesthetized rabbit results in full thickness corneal damage with apoptosis of corneal epithelium, keratocytes, and corneal endothelial cells. Apoptosis of corneal epithelial cells, visualized by TUNEL staining and confirmed by electron microscopy, peaked at 24 hours post-UVR, as was seen in the current study; by 72 hours postexposure, keratocytes were completely absent from the exposed region of the cornea (Podskochy et al, 2000). By 7 days there was TOXICOLOGIC PATHOLOGY almost complete repopulation of the injured stroma by new keratocytes (Podskochy and Fagerholm, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…There is definitive evidence that UV irradiation at wavelengths in the range from 280 to 310 nm induces apoptosis in the corneal epithelium based on terminal deoxynucleotidyl transferase (TdT)-mediated dUTP nick-end labeling (TUNEL)-positive staining in the intact rabbit and rat corneas (Tronnier, 1980;Podskochy et al, 2000;. Recently, it has been shown that exposure to UV is the leading cause of post-PRK corneal epithelial detachment and death (Nagy et al, 1995(Nagy et al, ,1997Wilson, 1997;Johnson et al, 1998).…”
Section: Uv Irradiation-induced Cellular Damagementioning
confidence: 99%
“…6). In doing so the corneal epithelium and lens protect the retina from UV irradiation-induced damage (Ringvold, 1998;Taylor et al, 1998;Podskochy et al, 2000). In addition, repeated subthreshold or single threshold UV-exposures lead to inhibition of mitosis, nuclear fragmentation and loss of the whole corneal epithelial layer.…”
Section: Uv Irradiation-induced Cellular Damagementioning
confidence: 99%
“…Indeed, the effect of UV light has been extensively investigated [1][2][3][4][5][6][7][8]. It has been reported that biotoxic epiphenomena may take place when the threshold level of radiation absorbed in corneal tissues is exceeded, and, consequently, permanent keratocyte damage or loss, epithelium destruction, endothelium edema and necrosis occur, as well as biochemical changes, such as ROS production, protein cross-linking, enzyme inactivation, DNA strand breaks and chemotactic factor release [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%